Behavioral corporate finance. Decisions that create value - SHEFRIN, Hersh (McGraw - Hill Book Company, 2007)
Behavioral Corporate Finance identifies the key psychological obstacles to value maximizing behavior, along with steps that managers can take to mitigate the effects of these obstacles. The main goal of the book is to help students learn how to put the traditional tools of corporate finance to their best use, and mitigate the effects of psychological obstacles that reduce value.